A pathologic study of carotid artery disease as an embolic source - Masuda, Junichi (Japanese Journal of Stroke, 2001)
Atherosclerosis in cervico-cephalic arteries is a lesion responsible for atherothrombotic brain infarcts. The pathological studies on the diversity of brain infarcts found in the autopsy cases with significant athero- sclerosis of the carotid arteries are summarized. All five autopsy cases with occlusive carotid thrombosis showed arterial territorial infarcts and no borderzone infarcts. Fifteen autopsy cases with atheromatous embolism in the brain, however, showed two types of brain infarcts (6 with arterial territorial infarct, 9 with bor-derzone infarct). This diversity of the lesion appeared to be correlated with histological features of the embolic materials (cholesterol crystal with or without other atheromatous components, especially fibrin). These variation in the components of the emboli may determine the size and location of the lodged arteries and feasibility of re-opening and hemorrhagic transformation. Recent development of transcranial Doppler and diffusion-weighted MRI enabled us to betect and follow-up very early stage of brain embolism and their silent recurrence, and may be valuable for clarifying the pathophysiology of brain embolism which occur based on the carotid atherosclerosis.